Cost-justifying usability an update for an Internet age - Bias, Randolph G.; Mayhew, Deborah J. (Amsterdam ; Boston : Morgan Kaufman, 2005)
You just know that an improvement of the user interface will reap rewards, but how do you justify the expense and the labor and the timeguarantee a robust ROI!ahead of time? How do you decide how much of an investment should be funded? And what is the best way to sell usability to others? In this completely revised and new edition, Randolph G. Bias (University of Texas at Austin, with 25 years experience as a usability practitioner and manager) and Deborah J. Mayhew (internationally recognized usability consultant and author of two other seminal books including The Usability Engineering Lifecycle) tackle these and many other problems. It has been updated to cover cost-justifying usability for Web sites and intranets, for the complex applications we have today, and for a host of productsoffering techniques, examples, and cases that are unavailable elsewhere. No matter what type of product you build, whether or not you are a cost-benefit expert or a born salesperson, this book has the tools that will enable you to cost-justify the appropriate usability investment. Includes contributions by a host of experts involved in this work, including Aaron Marcus, Janice Rohn, Chauncey Wilson, Nigel Bevan, Dennis Wixon, Clare-Marie Karat, Susan Dray, Charles Mauro, and many others; Includes actionable ideas for every phase of the software development process; Includes case studies from inside a variety of companies; Includes ideas from "the other side of the table," software executives who hold the purse strings, who offer thoughts on which proposals for usability support they've funded, and which ones they've declined.
Introduction: -- 1. Justifying cost-justifying usability -- 2. Return on investment for usable user-interface design: Examples and statistics -- Framework: -- 3. A basic framework for cost-justifying usability engineering on Web development projects -- 4. A business case approach to usability -- 5. Marketing usability -- 6. Dot coms -- Organizational and Design Context: -- 7. Cost-justification of usability engineering: A vendors perspective -- 8. Practical ROI issues for UCD teams: Considering the impact of social, internal, and external ROI on team credibility, team longevity, and product success -- 9. Usability science as an independent research service -- 10. ROI in Human Factors for Web Applications -- 11. The business case for international user centered design -- 12. Cost-justification of usability engineering for international Web sites -- 13. The ROI of accessibility -- Methods and Approaches: -- 14. Ethnography/Field research at Microsoft -- 15. Out of the box: Approaches to good initial interface designs; -- 16. Keystroke level modeling as a cost-justification tool -- 17. The RITE method -- 18. Sample size and user testing how much is enough? -- 19. Cost-justifying online surveys -- 20. Cost benefits framework and case studies -- 21. Want respect? Respect the shareholder: Usability at Sprint -- 22. Conclusion, wrap-up, next steps.
Includes bibliographical references and index.
Keywords: User interfaces (computer systems).; Value analysis (Cost control).; Electronic books